2014
DOI: 10.21829/myb.2014.202166
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between chemical compounds and mechanical response in culms of two different ages of Guadua angustifolia Kunth

Abstract: Wet chemical analysis was used to determine carbohydrate structural contents, as well as ash and extractive contents on four Guadua Angustifolia Kunth forms (f. Cebolla, f. Macana, f. Rayada Amarilla and f. Castilla) with two different growth ages (young and mature). Soluble and insoluble fiber content was determined by using AOAC 985.29 method. Bending tests were conducted in a universal testing machine following ASTM D143 standard method in order to determine modulus of rupture (MOR). Finally, a correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
4
3
0
Order By: Relevance
“…It is also possible define from the Figure 2 that Macana variety has a higher insoluble fiber content in each bamboo culm section than Rayada Amarilla; however, as a whole, insoluble fiber content is higher in Guadua angustifolia Rayada Amarilla as was shown in Table 1. As was found by Wang et al (2011) and Sanchez-Echeverri et al (2014) the mechanical response in bamboo culms is a correlation between both fibers; therefore, according with that results Macana culms are more appropriated for structural applications while Rayada Amarilla could be thinking for other applications such cellulose and pulp production.…”
Section: Fiber Determinationsupporting
confidence: 70%
See 1 more Smart Citation
“…It is also possible define from the Figure 2 that Macana variety has a higher insoluble fiber content in each bamboo culm section than Rayada Amarilla; however, as a whole, insoluble fiber content is higher in Guadua angustifolia Rayada Amarilla as was shown in Table 1. As was found by Wang et al (2011) and Sanchez-Echeverri et al (2014) the mechanical response in bamboo culms is a correlation between both fibers; therefore, according with that results Macana culms are more appropriated for structural applications while Rayada Amarilla could be thinking for other applications such cellulose and pulp production.…”
Section: Fiber Determinationsupporting
confidence: 70%
“…In the last three decades, bamboo has increased in importance around the world because of its mechanical, esthetic, and ecological properties, making it versatile for many applications. Moreover, the wide variety in appearance and chemical composition are some of the reasons why bamboo is more attractive, even than wood, for several purposes (SANCHEZ-ECHEVERRI et al, 2014). Not only the uses of bamboo as structural material are studied; some studies have shown the importance of bamboo leaves as pozzolanic materials to remove Cadmium I (Cd(I)) ions from aqueous solution (VILLAR-COCIÑA et al, 2011;PANDEY et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, forages with higher contents of crude protein, N-free extract (total carbohydrates excluding the crude fiber), and ether extract and low amounts of crude fiber are also preliminary indications that help to evaluate the forage quality (Mandal and Gautam 2012). -Echeverri et al 2014). In the present study, the content of CP in culms was lower than leaves.…”
Section: Nutritional Potential Of Merostachys Neesiisupporting
confidence: 50%
“…Other minor components like mannan, arabinan, and galactan were also detected as shown in Figure 7d. Previous studies [110,111] have shown that the biomechanical properties of the biomass tissues are highly correlated with composition. A significant reduction in lignin and glucan in RG could be due to reduced lignin and cellulose deposition in the sclerenchyma and vascular bundle cells [112].…”
Section: Py-gcms and Dfrc Analysismentioning
confidence: 98%